Tantangan Pelestarian Budaya Lokal dan Kesadaran Sosial Masyarakat terhadap Lingkungan di Era Globalisasi - Nazwa Nurkholifatululya Ajhari; Anggi Nagita Sharani; Rian Dwi Nugraha; Eka Eka; Reva Fadilatul Najah; Rijal Faturohman; Manda Manda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Globalization presents both opportunities and challenges for preserving local culture and raising environmental awareness. Rapid technological development and information flows can shift cultural values, weaken local wisdom, and encourage consumerist lifestyles that reduce environmental attention. Conversely, digital technology and social media offer tools to support cultural preservation, engage youth, and expand environmental education. Key strategies include environmental outreach, character-based education, implementing the 3R principles (Reduce, Reuse, Recycle), and collaboration among government, communities, cultural groups, and youth. Flexible and sustainable approaches are needed to maintain cultural identity and foster environmental awareness amid globalization.